A Robust Iterative Learning Control for Continuous-Time Nonlinear Systems With Disturbances - Pierallini, Michele; Angelini, Franco; Mengacci, Riccardo; Palleschi, Alessandro; Bicchi, Antonio; Garabini, Manolo (IEEE Access, 2021)

A real-time identification and tracking method for the musculoskeletal model of human arm - C. Fang; A. Ajoudani; A. Bicchi; N. G. Tsagarakis (2018 IEEE International Conference on Systems, Man, and Cybernetics (SMC), 2019)

Relaying the High-Frequency Contents of TactileFeedback to Robotic Prosthesis Users: Design,Filtering, Implementation, and Validation - S. Fani; K. Di Blasio; M. Bianchi; M. G. Catalano; G. Grioli; A. Bicchi (IEEE Robotics and Automation Letters, 2019)

On the role of postural synergies for grasp force generation and upper limb motion control - G. Averta; F. Angelini; A. Bicchi; G. Valenza; M. Bianchi (International Conference on NeuroRehabilitation, 2018)

Reduced-Complexity Representation of the Human Arm Active Endpoint Stiffness for Supervisory Control of Remote Manipulation - A. Ajoudani; C. Fang; N. G. Tsagarakis; A. Bicchi (International Journal of Robotics Research, 2017)

The Rice Haptic Rocker: skin stretch haptic feedback with the Pisa/IIT SoftHand - E. Battaglia; J. P. Clark; M. Bianchi; M. G. Catalano; A. Bicchi; M. K. O'Malley (IEEE World Haptics Conference, 2017)
Myoelectric prostheses have seen increased application in clinical practice and research, due to their potential for good functionality and versatility. Yet, myoelectric prostheses still suffer from a lack of intuitive control and haptic feedback, which can frustrate users and lead to abandonment. To address this problem, we propose to convey proprioceptive information for a prosthetic hand with skin stretch using the Rice Haptic Rocker. This device was integrated with the myo-controlled version of Pisa/IIT SoftHand and a size discrimination test with 18 able bodied subjects was performed to evaluate the effectiveness of the proposed approach. Results show that the Rice Haptic Rocker can be successfully used to convey proprioceptive information. A Likert survey was also presented to the experiment participants, who evaluated the integrated setup as easy to use and effective in conveying proprioception.
The authors gratefully acknowledge Matteo Rossi for his valuable advice and Mikaela Juzswik for her unique contribution in the physical realization of some of the equipment used in the experiments. This work was partially supported by the European Community funded project WEARHAP (contract 601165), by the European Commission project (Horizon 2020 research program) SOFTPRO (no. 688857), by the ERC Advanced Grant no. 291166 SoftHands and by the NSF grant IIS-1065497.
Keywords: Haptics

On the Role of Affective Properties in Hedonic and Discriminant Haptic Systems - M. Bianchi; G. Valenza; A Lanata; A. Greco; M. Nardelli; A. Bicchi; E. P. Scilingo (International Journal of Social Robotics, 2017)
Common haptic devices are designed to effectively provide kinaesthetic and/or cutaneous discriminative inputs to the users by modulating some physical parameters. However, in addition to this behavior, haptic stimuli were proven to convey also affective inputs to the brain. Nevertheless, such affective properties of touch are often disregarded in the design (and consequent validation) of haptic displays. In this paper we present some preliminary experimental evidences about how emotional feelings, intrinsically present while interacting with tactile displays, can be assessed. We propose a methodology based on a bidimensional model of elicited emotions evaluated by means of simple psychometric tests and statistical inference. Specifically, affective dimensions are expressed in terms of arousal and valence, which are quantified through two simple one-question psychometric tests, whereas statistical inference is based on rank-based non-parametric tests. In this work we consider two types of haptic systems: (i) a softness display, FYD-2, which was designed to convey purely discriminative softness haptic stimuli and (ii) a system designed to convey affective caress-like stimuli (by regulating the velocity and the strength of the “caress”) on the user forearm. Gender differences were also considered. In both devices, the affective component clearly depends on the stimuli and it is gender-related. Finally, we discuss how such outcomes might be profitably used to guide the design and the usage of haptic devices, in order to take into account also the emotional component, thus improving system performance.
Keywords: Haptics

Reflex Control of the Pisa/IIT SoftHand during Object Slippage - A. Ajoudani; E. Hocaoglu; Altobelli, A; M. Rossi; E. Battaglia; N G Tsagarakis; A. Bicchi (IEEE International Conference of Robotics and Automation (ICRA2016), 2016)
In this work, to guarantee the Pisa/IIT SoftHand’s grasp robustness against slippage, three reflex control modes, namely Current, Pose and Impedance, are implemented and experimentally evaluated. Towards this objective, ThimbleSense fingertip sensors are designed and integrated into the thumb and middle fingers of the SoftHand for real-time detection and control of the slippage. Current reflex regulates the restoring grasp forces of the hand by modulating the motor’s current profile according to an update law. Pose and Impedance reflex modes instead replicate this behaviour by implementing an impedance control scheme. The difference between the two latter is that the stiffness gain in Impedance reflex mode is being varied in addition to the hand pose, as a function of the slippage on the fingertips. Experimental setup also includes a seven degrees-of-freedom robotic arm to realize consistent trajectories (e.g. lifting) among three control modes for the sake of comparison. Different test objects are considered to evaluate the efficacy of the proposed reflex modes in our experimental setup. Results suggest that task-appropriate restoring forces can be achieved using Impedance reflex due to its capability in demonstrating instantaneous and rather smooth reflexive behaviour during slippage. Preliminary experiments on five healthy human subjects provide evidence on the similarity of the control concepts exploited by the humans and the one realized by the Impedance reflex, highlighting its potential in prosthetic applications.
Keywords: Haptics; Robotics

Robust Optimization of System Compliance for Physical Interaction in Uncertain Scenarios - Gasparri, G. M.; F. Fabiani; M. Garabini; L. Pallottino; M. G. Catalano; G. Grioli; R. Persichini; A. Bicchi (IEEE International Conference on Humanoid Robots (HUMANOIDS2016), 2016)
Compliance in robot design and control is often introduced to improve the robot performance in tasks where interaction with environment or human is required. However a rigorous method to choose the correct level of compliance is still not available. In this work we use robust optimization as a tool to select the optimal compliance value in a robotenvironment interaction scenario under uncertainties. We propose an approach that can be profitably applied on a variety of tasks, e.g.manipulation tasks or locomotion tasks. The aim is to minimize the forces of interaction considering model constraints and uncertainties. Numerical results show that: i) in case of perfect knowledge of the environment stiff robots behave better in terms of force minimization, ii) in case of uncertainties the optimal stiffness of the robot is lower than the previous case and optimal solutions provide a faster task accomplishment, iii) the optimal stiffness decreases as a function of the uncertainty measure. Experiments are carried out in a realistic set-up in case of bi-manual object handover.
This work was supported by the European Commission projects (FP7 framework) Walk-Man and the European Commission Grant no. H2020- ICT-645599 “SOMA”: SOft MAnipulation
Keywords: Robotics

A Reduced-Complexity Description of Arm Endpoint Stiffness with Applications to Teleimpedance Control - A. Ajoudani; C. Fang; N G Tsagarakis; A. Bicchi (IEEE International Conference of Intelligent Robots and Systems - IROS2015, 2015)
Effective and stable execution of a remote task in an uncertain environment requires that the task force and position trajectories of the slave robot be appropriately commanded. To achieve this goal, in teleimpedance control, a reference command which consists of the stiffness and position profiles of the master is computed and realized by the compliant slave robot in real-time. This highlights the need for a suitable and computationally efficient tracking of the human limb stiffness profile in real-time. In this direction, based on the observations in human neuromotor control which give evidence on the predominant use of the arm configuration in directional adjustments of the endpoint stiffness profile, and the role of muscular co-activations which contribute to a coordinated stiffening of the task stiffness in all directions, we propose a novel and computationally efficient model of the arm endpoint stiffness behaviour. With the purpose of real-time tracking of the human arm kinematics, an arm triangle is introduced using three body markers at the shoulder, elbow and wrist joints. In addition, a co-contraction index is defined using muscular activities of a dominant antagonistic muscle pair. Calibration and identification of the model parameters are carried out experimentally, using perturbation-based arm endpoint stiffness measurements in different arm configurations and co-contraction levels of the chosen muscles. Results of this study suggest that the proposed model enables the master to naturally execute a remote task by modulating the direction of the major axes of the endpoint stiffness and its volume using arm configuration and the co-ativation of the involved muscles, respectively.
softhands, wearhap
Keywords: Haptics; Robotics

On the Role of Robot Configuration in Cartesian Stiffness Control - A. Ajoudani; N G Tsagarakis; A. Bicchi (IEEE International Conference on Robotics and Automation (ICRA2015), 2015)
Keywords: Robotics

A real time robust observer for an agonist antagonist variable stiffness actuator - T. Menard; G. Grioli; A. Bicchi (IEEE International Conference on Robotics and Automation (ICRA2013), 2013)
Best Paper Award Finalist
Keywords: Robotics

On the Robust Synthesis of Logical Consensus Algorithms for Distributed Intrusion Detection - A. Fagiolini; A. Bicchi (Automatica, 2013)
Keywords: Embedded Control; Robotics

A Real-time Parametric Stiffness Observer for VSA devices - G. Grioli; A. Bicchi (2011 IEEE International Conference on Robotics and Automation, 2011)
Keywords: Robotics

Robust Network Agreement on Logical Information - S. Martini; D. Di Baccio; A. Fagiolini; A. Bicchi (2011 Congress of the International Federation of Automatic Control - IFAC 2011, 2011)
Keywords: Embedded Control; Robotics

On the Role of Hand Synergies in the Optimal Choice of Grasping Forces - M Gabiccini; A. Bicchi; D Prattichizzo; M. Malvezzi (Autonomous Robots [special issue on RSS2010], 2011)
Keywords: Haptics; Robotics

Rendering Softness: Integration of kinaesthetic and cutaneous information in a haptic device - E. P. Scilingo; M. Bianchi; G. Grioli; A. Bicchi (Transactions on Haptics, 2010)
Best Student Paper and Best Paper Award Finalist
Keywords: Haptics; Robotics

On the Role of Hand Synergies in the Optimal Choice of Grasping Forces - M Gabiccini; A. Bicchi (Robotics Science and Systems, 2010)
Keywords: Haptics; Robotics

Rendering softness: a new fabric yielding display - M. Bianchi; A. Serio; E. P. Scilingo; A. Bicchi (Workshop for young researchers on human - friendly robotics - Symposium, 2009)
Keywords: Haptics; Robotics

A Rough-Terrain, Casting Robot for the ESA Lunar Robotics Challenge - S. Alicino; M. G. Catalano; F. Bonomo; F. A. W. Belo; G. Grioli; R. Schiavi; A. Fagiolini; A. Bicchi (Proc. IEEE/RSJ International Conference on Intelligent RObots and Systems, 2009)
This paper describes the design and implementation of DAVID, a lunar vehicle developed for the European Space Agency (ESA) Lunar Robotics Challenge, presenting severe terrain negotiation and sample acquisition challenges. We discuss in some detail two of the main innovative aspects of our entry to the challenge, i.e. the locomotion system and the sample acquisition system. Motivated by the challenge specifications, a range of different locomotion systems were considered, among which we chose a simple, rugged and effective wheeled system. We provide an account of the choice of five different types of wheels, which were designed, analyzed and experimentally tested in conditions similar to the challenge. The system eventually turned out to be very effective in negotiating 89% slopes of volcanic terrain on the challenge site, Mount Teide in Tenerife. To reduce the distance to be traveled on the difficult terrain and avoid risks in reaching the lowest parts of a crater, the vehicle was endowed with an innovative sample acquisition system, i.e. a casting manipulator. Casting manipulation is a technique in which the end-effector is thrown, the sample material is acquired, and the end-effector is retrieved using a light tether that acts as a
Keywords: Robotics

Robust Almost Sure Stability for Uncertain Stochastically Scheduled Anytime Controllers - D. Fontanelli; L. Greco; A. Bicchi (Control and Automation, 16 th Mediterranean Conference on Control and Automation, 2008)
In this paper we consider closed loop stability of a number of different software tasks implementing a hierarchy of real-time controllers for a given plant, i.e.
Keywords: Robotics

Randomized Algorithms for Platform–based Design - A. Agostini; A. Balluchi; A. Bicchi; B. Piccoli; Sangiovanni Vincentelli, A.; K. Zadarnowska (Proc. IEEE Int. Conf. on Decision and Control, 2005)
The design of automotive control systems is becoming increasingly complex as the level of performance required by car manufactures grows continuously and the constraints on cost and development time imposed by the market become tighter. A successful design, without costly and time consuming re-design cycles, can be achieved only by using an efficient design methodology that allows for component re-use and evaluation of platform requirements at the early stages of the design flow. In this paper, we illustrate a control-implementation design methodology for the development of embedded controllers by composition of algorithms picked up from libraries. Randomized algorithms and hybrid system theory are used to develop techniques for functional and architecture evaluations, which are implemented in a prototype tool.
Keywords: Embedded Control; Robotics

Reachability and Steering of Rolling Polyhedra: A Case Study in Discrete Nonholonomy - A. Bicchi; Y. Chitour; A. Marigo (IEEE Trans. on Automatic Control, 2004)
Rolling a ball on a plane is a standard example of nonholonomy reported in many textbooks, and the problem is also well understood for any smooth deformation of the surfaces. For non-smoothly deformed surfaces, however, much less is known. Although it may seem intuitive that nonholonomy is conserved (think e.g. to polyhedral approximations of smooth surfaces), current definitions of ``nonholonomy'' are inherently referred to systems described by ordinary differential equations, and are thus inapplicable to such systems. \İn this paper we study the set of positions and orientations that a polyhedral part can reach by rolling on a plane through sequences of adjacent faces. We provide a description of such reachable set, discuss conditions under which the set is dense, or discrete, or has a compound structure, and provide a method for steering the system to a desired reachable configuration, robustly with respect to model uncertainties. \\Based on ideas and concepts encountered in this case study, and in some other examples we provide, we turn back to the most general aspects of the problem and investigate the possible generalization of the notion of (kinematic) nonholonomy to non-smooth, discrete, and hybrid dynamical systems. To capture the essence of phenomena commonly regarded as ``nonholonomic'', at least two irreducible concepts are to be defined, of ``internal'' and ``external'' nonholonomy, which may coexist in the same system. These definitions are instantiated by examples.
Keywords: Embedded Control; Robotics

A Robotic Set-Up with Remote Access for ``Pick and Place'' Operations Under Uncertainty Conditions - A. Balestrino; A. Bicchi; A. Caiti; T. Cecchini; L. Pallottino; A. Pisani; G. Tonietti (E-learning and Virtual and Remote Laboratories, 2004)
The work describes on-going work at the University of Pisa on the field of tele-laboratories and distance learning. In particular, the group is working at the evolution of existing tele-laboratory experiments in the field of robotics and control into learning units of a self-consistent didactic project. The pick-and-place system described has been designed to provide the set-up for robot arm motion planning with specific objectives and evaluation tools.
Keywords: Robotics

Receding-Horizon Control of LTI Systems with Quantized Inputs - B. Picasso; S. Pancanti; A. Bemporad; A. Bicchi (Analysis and Design of Hybrid Systems 2003, 2003)
This paper deals with the stabilization problem for a particular class of hybrid systems, namely discrete-time linear systems subject to a uniform (a priori fixed) quantization of the control set. Results of our previous work on the subject provided a description of minimal (in a specific sense) invariant sets that could be rendered maximally attractive under any quantized feedback strategy. In this paper, we consider the design of stabilizing laws that optimize a given cost index on the state and input evolution on a finite, receding horizon. Application of Model Predictive Control techniques for the solution of similar hybrid control problems through Mixed Logical Dynamical reformulations can provide a stabilizing control law, provided that the feasibility hypotheses are met. In this paper, we discuss precisely what are the shortest horizon length and the minimal invariant terminal set for which it can be guaranteed a stabilizing MPC scheme. The final paper will provide an example and simulations of the application of the control scheme to a practical quantized control problem.
Keywords: Embedded Control; Robotics

On the reachability of quantized control systems - A. Bicchi; A. Marigo; B. Piccoli (IEEE Trans. on Automatic Control, 2002)
In this paper we study control systems whose input sets are quantized, i.e. finite or regularly distributed on a mesh. We specifically focus on problems relating to the structure of the reachable set of such systems, which may turn out to be either dense or discrete. We report results on the reachable set of linear quantized systems, and on a particular but interesting class of nonlinear systems, i.e. nonholonomic chained-form systems. For such systems, we provide a complete characterization of the reachable set, and, in the case the set is discrete, a computable method to completely and succinctly describe its structure. Implications and open problems in the analysis and synthesis of quantized control systems are addressed.
Keywords: Embedded Control; Robotics

Risoluzione ottima dei conflitti tra agenti autonomi: applicazione al controllo del traffico aereo - L. Pallottino; A. Bicchi (Proc. 1st. Natl. Conf. and Exhibit on Autonomous Intelligent Systems and Advanced Robotics, 2002)
Keywords: Embedded Control; Robotics

Ramsete: Articulated and mobile robots for services and Technology (Springer-Verlag, 2001)
Keywords: Autonomous Vehicles; Robot Arms

Randomized parallel simulation of constrained multibody systems for VR/haptic applications - A. Bicchi; L. Pallottino; M. Bray; P. Perdomi (Proc. IEEE Int. Conf. on Robotics and Automation, 2001)
In this paper, we consider the problem of efficiently simulating large interconnected mechanical systems. For applications such as haptic rendering of large, complex virtual environments, dynamic simulation software and hardware is still too slow to afford accurate performance in real-time. In particular, mechanisms with closed kinematic chains necessitate solutions to a set of differential equation with algebraic constraints (DAE's), that are often too heavy and stiff to be computed in real-time by present-day single-processor machines. On the other hand, the structure of most state-of-the-art algorithms does not easily lend itself to parallelization. In this paper, we propose and experimentally verify a technique for DAE simulation that profitably uses a degree of randomization to achieve efficient parallelization.
Keywords: Dynamics and Simulation for Virtual Reality; Haptics

Robotic Grasping and Manipulation - A. Bicchi; V. Kumar (Ramsete: Articulated and mobile robots for services and Technology, 2001)
Keywords: Grasping; Haptics; Robot Hands

Reachability Analysis for a Class of Quantized Control Systems - A. Marigo; B. Piccoli; A. Bicchi (Proc. IEEE Int. Conf. on Decision and Control, 2000)
Keywords: Hybrid and Embedded Control Systems; Nonlinear Control Systems; Quantized Control Systems

Robotic Grasping and Contact: A Review - A. Bicchi; V. Kumar (Proc. IEEE Int. Conf. on Robotics and Automation, 2000)
Keywords: Grasping; Haptics; Robot Hands

Rolling Bodies with Regular Surface: Controllability Theory and Applications - A. Marigo; A. Bicchi (IEEE Trans. on Automatic Control, 2000)
Keywords: Nonlinear Control Systems; Robot Hands

Rolling Contacts and Dextrous Manipulation - A. Bicchi; A. Marigo (Proc. IEEE Int. Conf. on Robotics and Automation, 2000)
Keywords: Nonholonomic Systems; Nonlinear Control Systems; Robot Hands

The Role of Contact Area Spread Rate in Haptic Discrimination of Softness - G. Ambrosi; A. Bicchi; D. De Rossi; E. P. Scilingo (Proc. IEEE Int. Conf. on Robotics and Automation, 1999)
Many applications in teleoperation and virtual reality call for the implementation of effective means of displaying to the human operator information on the softness and other mechanical properties of objects being touched. The ability of humans to detect softness of different objects by tactual exploration is intimately related to both kinesthetic and cutaneous perception, and haptic displays should be designed so as to address such multimodal perceptual channel. Unfortunately, accurate detection and replication of cutaneous information in all its details appears to be a formidable task for current technology, causing most of today's haptic displays to merely address the kinesthetic part of haptic information. In this paper we investigate the possibility of surrogating detailed tactile information for softness discrimination, with information on the rate of spread of the contact area between the finger and the specimen. Devices for implementing this new perceptual channel are described, and some preliminary psychophysical test results are reported, validating the effectiveness and practicality of the proposed approach.
Keywords: Bioengineering; Haptics; Robotics

Rolling bodies with regular surfaces: the holonomic case - A. Marigo; A. Bicchi (Differential geometry and control, 1999)

Robotic Dexterity via Nonholonomy - A. Bicchi; A. Marigo; D Prattichizzo (Control Problems in Robotics and Automation, 1997)
Keywords: Haptics; Robotics

Rolling Polyhedra on a Plane: Analysis of the Reachable Set - Y. Chitour; A. Marigo; D Prattichizzo; A. Bicchi (Algorithms for Robotic Motion and Manipulation, 1997)
Keywords: Embedded Control; Robotics

Reachability of Rolling Parts - Y. Chitour; A. Marigo; D Prattichizzo; A. Bicchi (Advances in Robotics: The ERNET Perspective, 1996)
Keywords: Haptics; Robotics

Reflex Control of Locomotion for a Four-Legged Vehicle with Leg Redundancy - A. Balluchi; A. Bicchi; G. Casalino; D Prattichizzo (Proc. IFAC World Congress, 1996)
Keywords: Autonomous Vehicles; Legged Vehicles

Robot Tactile Perception - G. Buttazzo; A. Bicchi; P. Dario (Sensor Based Robots: Algorithms and Architectures, 1992)
Keywords: Haptics; Robotics

Robotic Tactile Sensing: Skin-like and Intrinsic Approach - A. Bicchi; G. Buttazzo (Intelligent Robotic Systems: Analysis, Design and Programming, 1991)
Keywords: Haptics; Robotics

A Robot Workstation for Autonomous Assembling - G. Buttazzo; M. Bergamasco; A. Bicchi; P. Dario (Proc. Int. Conf. on Robot Vision and Sensory Control, 1989)
Keywords: Robot Hands